2022
DOI: 10.1039/d2an01366e
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a broad-specific monoclonal antibody and development of an immunochromatographic assay for monitoring of anthranilic diamides in vegetables and fruits

Abstract: Anthranilic diamide insecticides, including chlorantraniliprole (CHL), cyantraniliprole (CYA), cyclaniliprole (CYC), and tetrachlorantraniliprole (TEA), are widely used in agricultural production, resulting in potential risk to human health. In this study, we...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Compared with the reported anti-CAP mAb (IC 50 , 1.6 ng/mL [18] and 1.5 ng/mL [19]), the sensitivity was improved 6.7-fold and 6.3-fold. Only cyclaniliprole and tetraniliprole showed CRs of 28.8% and 0.3%, respectively, because they have an antraniloiyl group (Table S2), and were similar to those reported previously (CR for cyclaniliprole was 37.5% [19,32].…”
Section: Characterization Of Anti-cap Mabsupporting
confidence: 87%
See 1 more Smart Citation
“…Compared with the reported anti-CAP mAb (IC 50 , 1.6 ng/mL [18] and 1.5 ng/mL [19]), the sensitivity was improved 6.7-fold and 6.3-fold. Only cyclaniliprole and tetraniliprole showed CRs of 28.8% and 0.3%, respectively, because they have an antraniloiyl group (Table S2), and were similar to those reported previously (CR for cyclaniliprole was 37.5% [19,32].…”
Section: Characterization Of Anti-cap Mabsupporting
confidence: 87%
“…Therefore, the CRs were 5% for tetraniliprole and 50% for cyclaniliprole using the AuNP-LFIA, which were similar to the The comparison between the AuNP-LFIA developed in this study and other methods for CAP is shown in Table S3. The sensitivity of the AuNP-LFIA in this study (visible LOD was 1.25 ng/mL) was improved 2-fold compared to the LFIA reported previously (visible LOD was 2.5 ng/mL) [32]. Although the proposed AuNP-LFIA had similar sensitivity to ELISAs [18,19], the detection time was reduced by more than 13-fold.…”
Section: Specificity Of the Aunp-lfiamentioning
confidence: 43%
“…Immunogen CBD hapten BSA (CBD-HS-BSA) and coating antigen CBD hapten ovalbumin (CBD-HS-OVA) were produced by coupling CBD-HS with BSA and OVA via an active ester method [35]. Activation solution was prepared by dissolving CBD (2.7 mg), N-hydroxysuccinimide (NHS, 1.5 mg), and 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC, 2.5 mg) in N, N-dimethylformamide (DMF, 0.5 mL) and stirring for 6 h at 25 • C. Then, the mixture was added slowly into BSA solution (20.0 mg of BSA added into 0.01 M PBS, 2 mL), stirred for 8 h, and subsequently dialyzed in PBS (pH 7.4) for 72 h at 4 • C to isolate CBD-HS-BSA.…”
Section: Preparation Of Antigenmentioning
confidence: 99%